MEGA: a real-time visualisation framework for large-scale terrain. (1st January 2012) - Guo, Haoran; Pang, Jianmin; Yu, Jintao; Shan, Zheng
Real-time simulation and rendering of large-scale terrain model is a hot research topic in fields such as 3D computer games, cartoon movies and flight simulation, etc. This paper presents mechanism of terrain data organisation and real-time (MEGA) rendering, a GPU-oriented, hybrid quantree-based large terrain visualisation framework. The present terrain data structure based on hybrid quadtree, which combines static full resolution and dynamic variable resolution quadtree to organise the whole terrain scene and reduce the level of detail at need. Another feature is taking advantage of GPU to achieve view-frustum culling and terrain blocks updating. We also introduce a GPU-based error metric method. At run time, screen space error is projected from geometric error and compared with error threshold according to viewpoint to select terrain blocks by GPU. This error metric method can improve the rendering efficiency of graphic hardware. MEGA shows a maximal speed increment of 38% for high-quality terrain rendering compare with other similar solutions.